Uptake and excretion of iron by healthy elderly subjects. Issue 12 (December 1984) - Bunker, V W; Lawson, M S; Clayton, B E
Abstract : Metabolic balance studies for iron have been carried out on 24 apparently healthy elderly people (11 men and 13 women) aged 69.7 to 85.5 years living in their own homes and eating self selected diets. Several biochemical and haematological indices of iron state were also measured. The mean daily iron intake was 176 mumol, with a range of 55-321 mumol. Eight women and six men consumed diets which provided less than the recommended daily dietary allowance for iron of 179 mumol/day. Mean daily retention of iron, however, was -7 mumol, a value which did not significantly differ from equilibrium. No sex difference was noted between any of the biochemical and haematological measurements. Mean values of iron concentration, iron binding capacity, iron binding saturation, and ferritin and haemoglobin concentrations were 20 mumol/l, 59 mumol/l, 34%, 77 micrograms/l, and 14.3 g/dl, respectively. We have shown that in apparently healthy elderly people who are in equilibrium for iron balance, several biochemical and haematological measurements of iron state do not differ from the normal ranges established in younger adults.